Corrigendum to “Subchronic Infection of Porphyromonas gingivalis and Tannerella forsythia Stimulates an Immune Response but Not Arthritis in Experimental Murine Model” - Hernández-Aguas, Jorday (2018)
In the article titled “Subchronic Infection of Porphyromonas gingivalis and Tannerella forsythia Stimulates an Immune Response but Not Arthritis in Experimental Murine Model”, there was an error in Table 1 where “Freud’s adjuvant” should be changed to “Freund’s adjuvant.” The formatting of the table is also being corrected for clarity. The correct table is as follows.